Development of Snack Containing Meat By-Products and its Nutritional Evaluation - Subba, Dilip (Tribhuvan University Journal, 2011)
Available with full text. Key words: Snack; Meat products; Liver; Spleen Tribhuvan University Journal Vol XXIII, No. 1, 2001 Page: 43-49 Uploaded date: 21 April, 2011